The Effect of Distribution and Product Quality on The Purchase Decision of Prim-A Mineral Water at PT Delada Cahaya Mas Agro Gunungsitoli With Brand Awareness as A Mediation Variable - Fredika Ade Pratama Agustiawan; Harefa, Idarni; Laia, Otanius; Mendrofa, Yupiter (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study examines the influence of distribution and product quality on purchasing decisions of Prim-A mineral water at PT. Delada Cahaya Mas Agro, with brand awareness as a mediating variable. The increasing competition in the bottled water industry requires companies not only to strengthen distribution networks but also to maintain product quality in order to build consumer trust and brand recognition. This research employs a quantitative approach using Partial Least Squares (PLS) with SmartPLS 4. A total of 100 respondents in Gunungsitoli were selected through accidental sampling. The findings indicate that distribution has a direct and significant positive effect on purchasing decisions (p-value < 0.05). Product quality, however, does not directly influence purchasing decisions (p-value > 0.05) but significantly affects them indirectly through brand awareness (p-value < 0.05), which acts as a full mediator. Brand awareness thus plays a critical role in linking product quality to consumer decision-making. The study suggests that companies should expand distribution reach while simultaneously implementing branding strategies to enhance awareness and consumer perception. The results provide theoretical implications for marketing management and practical recommendations for local distributors competing with established national brands such as Aqua and Le Minerale.